PENGARUH BAURAN PROMOSI TERHADAP VOLUME PENJUALAN HOLCIM SOLUSI RUMAH BINTANG JAYA DI JEMBER - Jeffrey Andi Kesuma* Karim Budiono** Bagus Qomaruzaman Ratu Edi*** (Universitas Muhammadiyah Jember, 2015)
This research aims to know about the significiance of simultaneous effect of the promotion mix (advertising, personal selling, sales promotion, public relations and direct marketing) to be analysis from 3 variabels are sales promotion, personal selling and advertising to increase volume sales of construction products at Holcim Solusi Rumah Bintang Jaya Jember and know the promotional mix construction products company Holcim Solusi Rumah Bintang Jaya Jember. The reserch model is a field research, the research done by going directly to the company to got primary data through observation and interviews with corporate leaders. Other research methods bused in this study is the research library carried out with a bovew related open issues, as well as theresults of other studies that can support this reseach. The analytical method used is multiple regression analysis,F test, t test and coefficient of determination. Multiple regression models used to describe the relationship between independent variables and the dependent variabel. F test is often called the simulotaneous test, which is used to test wheter the independent variables used in the model can explain the change in the value of the dependent variable or not. t test used to determine the effect of each independent variable consisting of sales promotion, personal selling, and advertising to sales volume. Coefficient determination used to indicate that the the over all of variable of independent have influence in explaining variation change of sales volume. The results indicate that the effect of Promotional mix on sales volume construction products at Holcim solusi rumah Bintang Jaya Jember have a significant effect with the Personal selling variables as variables having an influence on the most significant increase in sales volume